Identifying Factors That Influence the Utilization of Agribazaar's Portal - Hussian, Dawood Sallem (2009)
This paper aims to evaluate the acceptance of Agribazaar's portal by users of the portal. The Unified Theory of Acceptance and Use of Technology (UTAUT) model has been used to assess user's acceptance on Agribazaar's portal. This model suggests that there are a number of factors that influence a user to use a new technology. A survey has been conducted online in Malaysia and 119 responds have been received on the results indicate that performance expectancy, effort expectancy, social influences, and facilitating conditions do the affects of the utilization of Agribazaar's portal. Finally, suggestion on the portal has been made so that the portal can be extensively used globally by agricultural community.